Increased expression of cell adhesion molecules in myofasciitis - Ma, Xue; Gao, Huajie; Xu, Li; Bi, Zhuajin; Ji, Suqiong; Bu, Bitao (Frontiers in Neurology, 2023)
Background: Myofasciitis is a heterogeneous group of diseases pathologically characterized by inflammatory cell infiltration into the fascia. Endothelial activation plays a critical role in the pathogenesis of the inflammatory response. However, the expression of cellular adhesion molecules (CAMs) in myofasciitis has not been investigated. Methods: Data on clinical features, thigh magnetic resonance imaging, and muscle pathology were collected from five patients with myofasciitis. Immunohistochemical (IHC) staining and Western blot (WB) of the muscle biopsies from patients and healthy controls were performed. Results: Increased levels of serum pro-inflammatory cytokines, including IL-6, TNF-α, and IL-2R, were detected in four patients. IHC staining and WB indicated significantly increased expression of cell adhesion molecules in blood vessels or inflammatory cells within the perimysium in muscle and fascia tissues of patients with myofasciitis compared to controls. Conclusion: The up-regulation of CAMs in myofasciitis indicates endothelial activation, which may be potential therapy targets for the treatment of myofasciitis.